Canine Parvoviral Enteritis - The Role of MMP-9 and TIMP-1 in the Pathogenesis of Intestinal Inflammation - Karayiğit, Mehmet Önder; Aydoğan, Ahmet; Halıgür, Mehmet; Başbuğ, Onur; Karataş, Özhan (Acta Scientiae Veterinariae, 2024)
Background: Canine parvoviral enteritis is a highly contagious infection in the intestines caused great morbidity and mortality in untreated dogs younger than 6 months. Matrix metalloproteinases consist of zinc- and calcium-dependent extracellular matrix-degrading endopeptidases that are tightly controlled by endogenous metalloproteinase tissue inhibitors. Canine parvoviral enteritis is common in Turkey. The aim of this study was to examine the expression of matrix metalloproteinase-9 (MMP-9) and tissue inhibitor of matrix metalloproteinases-1 (TIMP-1) in natural canine parvoviral enteritis infection of 25 dogs diagnosed with parvoviral enteritis by clinical tests and histopathology. Materials, Methods & Results: The study material consists of dog’s small intestine, which was brought to Cumhuriyet University Faculty of Veterinary Medicine pathology department for necropsy and diagnosed with parvoviral enteritis. This investigation was suported by the Comission of Scientific Research Projects of Cumhuriyet University (Project No: V-086). For the study, sections of 5 μm were taken from small intestine blocks consisting of duodenum, jejunum and ileum, fixed in 10% buffered formalin solution and embedded in paraffin, and stained with hematoxylin-eosin and MMP-9 and TIMP-1 antibodies using immunohistochemical procedure. On histopathology, shedding and blunting of the villi epithelium, severe mononuclear inflammation in the lamina propria and locally enlarged crypts with lymphocytolysis in peyer's patches were noted in the ileum. Immunohistochemically, strong expression for MMP-9 and moderate expression for TIMP-1 were observed in the crypt epithelium and inflammatory cells in the small intestines of infected animals compared controls (P < 0.001). Discussion: In the present study, immunohistochemical expressions of MMP-9 and TIMP-1 in intestinal tissues were investigated in canine parvoviral enteritis, which is an important viral disease in veterinary medicine. Statistically strong expression for MMP-9 and moderate expression for TIMP-1 were observed in the crypt epithelium and inflammatory cells in the small intestines of infected animals. As a result, high levels of MMP-9 may be one of the factors that trigger the inflammatory process in the disease. It is thought that the increase in MMP-9 may be directly proportional to the severity of inflammation in the tissue. In addition, it is suggested that the level of its inhibitor, TIMP-1, may increase at similar rates in response to this increase in MMP-9 levels. As a result, severe increases MMP-9 and TIMP-1 may indicate the presence of inflammation of similar severity in that tissue. Immunohistochemical data obtained from the study showed that MMP-9 expression was found to increase in inflammatory and degenerative changes in parvoviral enteritis. This may have triggered extracellular matrix degradation, intestinal permeability, degenerative changes and inflammation. Abnormal increase in MMP-9 levels is thought to contribute significantly to the intestinal lesions in parvoviral enteritis. It was observed that TIMP-1 levels increased similarly in response to this increase but weaker expression of TIMP-1 as its inhibitor in canine parvoviral enteritis may determine the development of the disease. In this regard, matrix metalloproteinases appear to be potential therapeutic targets in canine parvoviral enteritis, and the use of their inhibitors can significantly reduce disease progression. However, current findings need to be confirmed by more detailed studies in the future. Keywords: dog, viral infection, metalloproteinase activity, MMP-9, parvoviral enteritis, TIMP-1.